2020
DOI: 10.1093/nar/gkaa278
|View full text |Cite
|
Sign up to set email alerts
|

Peptides containing the PCNA interacting motif APIM bind to the β-clamp and inhibit bacterial growth and mutagenesis

Abstract: In the fight against antimicrobial resistance, the bacterial DNA sliding clamp, β-clamp, is a promising drug target for inhibition of DNA replication and translesion synthesis. The β-clamp and its eukaryotic homolog, PCNA, share a C-terminal hydrophobic pocket where all the DNA polymerases bind. Here we report that cell penetrating peptides containing the PCNA-interacting motif APIM (APIM-peptides) inhibit bacterial growth at low concentrations in vitro, and in vivo in a bacterial skin infection model in mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…To exclude that this anti-biofilm effect was due to the cell penetrating part of the APIM-peptide, we included the 11-arginine cell penetrating peptide, R11, as a control. However, 60 μM of the R11 peptide gave only ∼1 log decrease in CFU/mL, showing that, similarly to the antibacterial and anti-mutagenic effects ( Nedal et al, 2020 ), the full-length peptide containing APIM is needed for maximal anti-biofilm effect. Preliminary data also shows that coating steel rods with APIM-peptide dissolved in polyethylene glycol (PEG) inhibited biofilm formation (data not shown); thus, APIM-peptides could potentially be exploited for further use in coating of surgical implants.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…To exclude that this anti-biofilm effect was due to the cell penetrating part of the APIM-peptide, we included the 11-arginine cell penetrating peptide, R11, as a control. However, 60 μM of the R11 peptide gave only ∼1 log decrease in CFU/mL, showing that, similarly to the antibacterial and anti-mutagenic effects ( Nedal et al, 2020 ), the full-length peptide containing APIM is needed for maximal anti-biofilm effect. Preliminary data also shows that coating steel rods with APIM-peptide dissolved in polyethylene glycol (PEG) inhibited biofilm formation (data not shown); thus, APIM-peptides could potentially be exploited for further use in coating of surgical implants.…”
Section: Resultsmentioning
confidence: 97%
“…The growing problem of antibacterial resistance highlights the need for new antibiotics with a novel mode of action. In this paper, the recently discovered antibacterial effect of APIM-peptides ( Nedal et al, 2020 ) and their potential use in a clinical setting with MRSE infections are explored. The results show that APIM-peptide kill S. epidermidis rapidly in in vitro planktonic cultures as well as in biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the authors showed that their CPPmodified peptide inhibited bacterial DNA replication and bacterial growth in a mouse skin infection model. This is an interesting find that has implications beyond cancer research and is important from the perspective of antimicrobial resistance [26].…”
Section: Targeting Protein-protein Interactionsmentioning
confidence: 89%